IMPLEMENTASI NILAI PANCASILA PADA TONGKRONGAN OLEH GENERASI Z DI KECAMATAN SIDOARJO - Krisnanda, Mikhael Ekklesia; Warsono (Universitas Negeri Surabaya (Unesa), 2024)
This research aims to analyze the implementation of Pancasila values in the social activities of Generation Z in Sidoarjo District. Generation Z, known for their technological literacy, exhibits unique characteristics in their social behavior, particularly in the context of